2009
DOI: 10.1029/2007je003052
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Electrical Conductivity Probe (TECP) for Phoenix

Abstract: [1] The Thermal and Electrical Conductivity Probe (TECP) is a component of the Microscopy, Electrochemistry and Conductivity Analyzer (MECA) payload on the Phoenix Lander. TECP will measure the temperature, thermal conductivity, and volumetric heat capacity of the regolith. It will also detect and quantify the population of mobile H 2 O molecules in the regolith, if any, throughout the polar summer, by measuring the electrical conductivity of the regolith as well as the dielectric permittivity. In the vapor ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 60 publications
0
66
0
1
Order By: Relevance
“…Values of temperature and RH covered in the pre-flight calibration (Zent et al 2009) overlap only partially with the environmental conditions found at the Phoenix landing site ). The calibration function was revised in 2016 to correct for inaccuracies at the lowest temperatures observed at the Phoenix landing site (Zent et al 2016), but the new processed RH values are not available in the PDS yet.…”
Section: Phoenix Missionmentioning
confidence: 99%
See 2 more Smart Citations
“…Values of temperature and RH covered in the pre-flight calibration (Zent et al 2009) overlap only partially with the environmental conditions found at the Phoenix landing site ). The calibration function was revised in 2016 to correct for inaccuracies at the lowest temperatures observed at the Phoenix landing site (Zent et al 2016), but the new processed RH values are not available in the PDS yet.…”
Section: Phoenix Missionmentioning
confidence: 99%
“…Of all spacecraft landed on Mars, only the PHX and MSL carried sensors to measure the near-surface relative humidity (Table 1) (Zent et al 2009;Gómez-Elvira et al 2012). For Among the full set of REMS RH measurements, only those taken during the first four seconds after the RHS has been turned on after at least ∼5 min of inactivity are considered here.…”
Section: Near-surface Relative Humidity and Water Vapor Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, in the frame of the Huyghens-Cassini mission, the thermal conductivity of Titan's atmosphere was determined by a probe working on the basis of the hot needle method (Hathi et al, 2007). However, the only space instrument that has measured thermal conductivity in the solid material of an extraterrestrial body other than the Moon was the TECP-instrument aboard the NASA Phoenix spacecraft, which landed on the Martian polar plains in 2008 (Zent et al, 2009(Zent et al, , 2010. The method used to evaluate the thermal conductivity measurements obtained from the TECP-instrument is described in Cobos et al.…”
Section: Introductionmentioning
confidence: 99%
“…The Phoenix lander ran a suite of surface and weather experiments in the martian northern polar region (at the location with coordinates latitude 68°N, longitude 234°E) from L s = 76.5°to 148°in MY29 (Smith et al, 2009b). In particular, the Phoenix lander Thermal and Electrical Conductivity Probe (TECP) (Zent et al, 2009;Zent, 2014) measured diurnal variations in the water vapor partial pressure (from $0.1-0.2 Pa at noon to $0.01-0.05 Pa at 2 am, corresponding to mixing ratio changes from $100 to $10 ppmm) within 2 m of the ground, which was interpreted as a manifestation of water vapor adsorption by the soil at night (Smith et al, 2009b). The Light Detection and Ranging (LIDAR) measurements (Whiteway et al, 2009) observed sporadic water ice clouds above 10 km altitude around L s = 90°.…”
Section: Atmospheric Modelmentioning
confidence: 99%